Floralozone protects endothelial function in atherosclerosis by ameliorating NHE1. (19th August 2021) - Huang, Ning; Qiu, Yue; Liu, Yanhua; Liu, Tianheng; Xue, Xianjun; Song, Ping; Xu, Jian; Fu, Yutian; Sun, Ruili; Yin, Yaling; Li, Peng
Abstract: Endothelial dysfunction is the pathological basis of atherosclerosis. Incomplete understanding of endothelial dysfunction etiology has impeded drug development for this devastating disease despite the currently available therapies. Floralozone, an aroma flavor, specifically exists in rabbit ear grass. Recently, floralozone has been demonstrated to inhibit atherosclerosis, but the underlying mechanisms are undefined. The present study was undertaken to explore whether floralozone pharmacologically targets endothelial dysfunction and therefore exerts therapeutic effects on atherosclerosis. The Na + /H + exchanger 1 (NHE1), a channel protein, plays a vital role in atherosclerosis. Whether NHE1 is involved in the therapeutic effects of floralozone on endothelial dysfunction has yet to be further answered. By performing oil red staining and hematoxylin–eosin staining, vascular functional study, and oxidative stress monitoring, we found that floralozone not only reduced the size of carotid atherosclerotic plaque but also prevented endothelial dysfunction in atherosclerotic rats. NHE1 expression was upregulated in the inner membrane of carotid arteries and H2 O2 -induced primary rat aortic endothelial cells. Inspiringly, floralozone prevented the upregulation of NHE1 in vivo and in vitro . Notably, the administration of NHE1 activator LiCl significantly weakened the protective effect of floralozone on endothelial dysfunction in vivo and in vitro . Our study demonstrated that floralozone exerted its protective effect on endothelial dysfunction in atherosclerosis by ameliorating NHE1. NHE1 maybe a drug target for the treatment of atherosclerosis, and floralozone may be an effective drug to meet the urgent needs of atherosclerosis patients by dampening NHE1.